Turkey : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Turkey. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses key issues related to Turkey's economy. Economic growth of Turkey continues to show resilience despite several shocks. Growth remains based on domestic demand, in turn, supported by accommodative monetary and fiscal policies. With the economy projected to grow at 3.8 percent in 2015, output and unemployment gaps are practically closed. But, growth is still below both the historical average and the authorities' long-term target. Potential growth is also slowing. The employment rate is low, especially among women. To tackle these issues, the government has announced ambitious program of reforms aiming to increase potential growth and reduce external imbalances.